2013
DOI: 10.1590/s1517-83822013000300007
|View full text |Cite
|
Sign up to set email alerts
|

Influence of phenolic compounds of Kangra tea [Camellia sinensis (L) O Kuntze] on bacterial pathogens and indigenous bacterial probiotics of Western Himalayas

Abstract: Phenolic compounds of nutraceutical importance viz., catechins (C), (−)-epicatechin (EC), (−)-epigallocatechin (EGC), (−)-epigallocatechin-3-gallate (EGCG) and (−)-epicatechin-3-gallate (ECG) were estimated in fresh green tea shoots of Camellia sinensis (L) O Kuntze cultivar. The total polyphenols and total catechins were in the range of 219.90 to 317.81 and 140.83 to 271.39 g/kg, respectively in monthly samples of tea. The values of C, EC, EGC, EGCG and ECG in tea powders as analyzed through high performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…The antibacterial activity of green tea extract was previously described, and the finding that it was related to the catechin content was noteworthy [14, 15]. Additionally, green tea extract was shown to be able to kill S. aureus and other harmful bacteria [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antibacterial activity of green tea extract was previously described, and the finding that it was related to the catechin content was noteworthy [14, 15]. Additionally, green tea extract was shown to be able to kill S. aureus and other harmful bacteria [26].…”
Section: Discussionmentioning
confidence: 99%
“…These compounds provide health benefits and show remarkable antimicrobial activity against resistant pathogens [13, 14]. Tea extracts having high concentrations of epigallocatechin gallate (EGCG) and epigallocatechin (EGC) are more potent in antibacterial activity against bacterial pathogens [15]. EGCG at concentrations between 78 and 625 μg/mL was able to inhibit Acinetobacter baumannii [16].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, our results confirmed that the chemical structure of polyphenols did indeed influence their effects on bacterial growth. In relation to this, other authors observed that flavanols with galloyl moiety ((−)-epigallocatechin, (−)-epicatechin-3-gallate and (−)-epigallocatechin-3-gallate) exhibited more activity on bacteria growth than those without galloyl moiety (catechins and (−)-epicatechin) [29]. Also, the microbial potency of polyphenols towards bacteria growth has also been reported to be dependent upon bacterial strain, species and genera [30], as we have also observed in our study.…”
Section: Effects Of Phenolic Compounds On the Lab Growthmentioning
confidence: 82%
“…Spot screening indicated that the presence of active biological compounds such as flavonoids, proteins, phenols, alkaloids, and glycosides also exhibited strong activity against tested bacterial strains (Bashir et al, 2014). Sourabh et al (2014). As is generally well known, the antimicrobial effect of plant extracts, including extract derived from Camellia spp.…”
Section: Resultsmentioning
confidence: 99%